The correlation between cranial fractures and brain trauma: a retrospective study - Sakambana, Sinoyolo (Department of Pathology, 2025)
Traumatic brain injury (TBI) is a global public health concern. TBI has been noted to co-occur with cranial fractures, however this is not always case. At present, there is a gap in literature regarding the correlative relationship between the presence of cranial fracture and brain trauma. The knowledge and understanding of this correlation is imperative for autopsy examinations where pathologists have to determine the cause of death of an individual. Furthermore, in cases where the skeleton is the only tissue that is available for examination, anthropologists will be able to apply this knowledge to infer the presence of brain trauma at death. Therefore, the current study aimed to assess the correlation of cranial fracture and brain injury in cases of blunt force trauma. This was achieved through a retrospective review of blunt force head injury cases of blunt force head injury examined at Salt River Mortuary, Cape Town between 01 January 2015 and 31 December 2019. Co-occurrence of cranial fractures with brain trauma was prevalent in the current study, accounting for 64% of the recorded cases. A significant association was found between age at death and the presence of brain trauma (p = 0.042), with majority of individuals with brain trauma ranging between 18 to 49 years of age. Similarly, a significant association was found between the presence of cranial fractures and age (p = <0.001). A significant association was found between the presence of cranial fractures and brain trauma to the frontal, parietal and temporal lobes (p = <0.001). Moreover, fracture type was significantly associated with the presence of brain trauma. Fractures of the cranial base have an increased risk of being associated with traumatic brain injury compared to the fractures in other regions. Individuals presenting with cranial fracture are 4.48 times more likely to have TBI, compared to those without cranial fracture. Specifically, individuals with fracture of the basal region of the cranium are 3.77 times more likely to have co-occurring TBI. Notably, all cases of hinge fractures had associated brain trauma. The data presented in this study can be used for the prediction of the presence of brain trauma, where the presence of cranial fracture is noted.